A comunicação científica da Região Norte nos congressos de Ecotoxicologia no Brasil: uma análise da evolução histórica do período 1991-2018 - CONCEIÇÃO, Amanda Pinheiro (2022)
The Ecotoxicology is a multidisciplinary science that studies the toxic effects of chemical compounds, as well as the fate and transport of substances in the environment. In Brazil, the Brazilian Society of Ecotoxicology brings together scientists in the field and regularly holds a national meeting of researchers, called the Brazilian Congress of Ecotoxicology (ECOTOX). Despite its environmental importance, the North region has had little representation in studies in this area. The present study aimed to carry out a bibliographical survey based on the annals of ECOTOX between the years 1991-2018 in order to assess the evolution of research in the Northern Region of the country, taking into account the main themes addressed in the abstracts. As a result, the North region presented a total of 213 abstracts published in the annals of ECOTOX, a value that represents approximately 4% of the total abstracts published in the events, with its representation in the states of Pará, Amazonas, Rondônia and Tocantins with 92, 63, 55 and 3 published abstracts respectively, while the other states did not present publications. Among the abstracts presented, it is known that most northern research is carried out in the aquatic, freshwater environment and with laboratory analysis, representing 69% of the studies. A theme that stood out in this study was 'Bioavailability, Bioaccumulation and Biomagnification', mainly in metal concentration studies. The low participation of states such as Tocantins, Amapá, Acre and Roraima denote that Ecotoxicology is not yet fully disseminated in the region, demanding research incentives for northern institutions and it is also necessary to encourage environmental education and scientific dissemination in the region, which, in the 30-year history of the congress, has presented only one abstract from the state of Pará and has only three research groups that carry out scientific dissemination. It is urgent that Ecotoxicology is disseminated to the general population and public managers through extension activities and environmental education, as this is the only way to gain greater visibility and support from civil society throughout Brazil.